The PRAISE Scale of Posttraumatic Growth: Development, Validation and Exploration of its Relationship with Trait Resilience - Lewandowski, Felix (2024)
Background: Individuals who adapt well to adversity (e.g., traumatic events) and recover quickly are often described as resilient. However, there are also individuals who report positive psychological changes beyond pre-adversity levels, referred to as posttraumatic growth (PTG). Existing research on the association between resilience and PTG yields conflicting results due to varied definitions and operationalisations of each construct. This thesis aims to explore whether trait resilience predicts the development of PTG over time. As the traditional approach to measuring PTG is widely criticised to assess perceptions of PTG rather than actual ‘veridical’ changes in pre-to-post functioning, the Possibilities, Relationships, Appreciation of Life, Strength, Existence (PRAISE) scale is developed and psychometrically validated to examine veridical PTG as trajectories of psychological functioning over time. The PRAISE scale is used to test the main research question of this thesis.